Five‐year soil moisture response of typical cultivated grasslands in a semiarid area: Implications for vegetation restoration. (21st January 2020) - Dang, Zhi‐Qiang; Huang, Ze; Tian, Fu‐Ping; Liu, Yu; López‐Vicente, Manuel; Wu, Gao‐Lin
Abstract: Soil water deficit is one of the important abiotic stresses affecting vegetation restoration. The magnitude and spatiotemporal dynamics of soil water content (SWC) provide basic guidance for optimal vegetation restoration. In a semiarid Chinese area, the changes in the soil water storage (SWS) of five cultivated grasslands and one wasteland were observed, to evaluate the water consumption at different soil depths (0–100 cm), from 2008 to 2012. The plants of the three leguminous species consumed more water in deep soil layers (80–100 cm) and produced more aboveground biomass than the plants of the two gramineous species. The gramineous plants mainly consumed shallow soil water (0 ≤ 30 cm). The soil water deficit in the whole soil profile of Medicago sativa grassland (43–48%) was significantly higher than the deficit of the gramineous grasslands ( p  < .05). After 5 years of planting, the SWC of Agropyron cristatum grassland (21%) was the highest in the 20‐ to 80‐cm soil layer. The variation of SWS in M. sativa grassland did not significantly differ during this period, although its mean value was 28% lower than the value in A. cristatum grassland (181 mm). At the end of the experiment, leguminous grasslands caused a serious soil water shortage deficit in the 80‐ to 100‐cm soil layers. These results underscore that vegetation type determines the vertical distribution of soil water deficit, particularly in deep layers. To promote long‐term sustainability of water resources, planting A. cristatum may be a good choice for early grassland restoration in arid areas.